LEGAL RESPONSIBILITY OF SINGERS OR PERFORMERS FOR THE USE OF SONGS THAT HAVE COPYRIGHT ACCORDING TO LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHT - Putri Rosita Damayanti; Abraham Ferry Rosando (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the legal liability of singers or performers for using copyrighted songs without the creator’s permission in commercial activities such as concerts. The main issue discussed is the legal responsibility of singers in performing copyrighted songs and the application of copyright infringement elements as reflected in Decision Number 92/Pdt.Sus-HKI/Hak Cipta/2024/PN Niaga Central Jakarta. This research applies a normative juridical approach by analyzing relevant legislation and court decisions. The findings indicate that singers are legally obligated to obtain permission from the creator or through a Collective Management Organization (LMK/LMKN) before performing a song commercially. Furthermore, concert promoters or organizers also share legal responsibility as they derive economic benefits from such performances. The enforcement of copyright law in the music industry requires synergy between creators, singers, and collective management organizations to establish a fair and balanced creative ecosystem